Magnetic multiparticulate colonic delivery systems evaluated by AC Biosusceptometry - Corá, L. A. [UNESP]; Fonseca, P. R. [UNESP]; Stelzer, M. [UNESP]; Paixão, F. C. [UNESP]; Romeiro, Fernando Gomes [UNESP]; Américo, M. F.; Baffa, O.; Oliveira, R. B.; Miranda, J. R A [UNESP] (Elsevier, 2007)
The biomagnetic technique called Alternate Current Biosusceptometry (ACB) is a proposal to evaluate a multiparticulate drug delivery system in the human gastrointestinal tract. Results show that ACB was able to quantify the gastrointestinal transit and spreading of the magnetic material and is an attractive tool for pharmaceutical research. © 2007.
Keywords: Biomagnetism; Controlled release; Magnetic image; Solid dosage form